Sposoby ubierania się i zachowania zakupowe jako forma komunikowania statusu społecznego = Modes of dress and shopping behavior as a form of communicating social status - Wielgosz, Szymon (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This paper explores the relationship between dressing habits and shopping behavior as a means of manifesting one`s social status. The aim of the study presented in the article is to identify and describe how adults of different social classes display their social status through apparel, including the garments they purchase, their preferred shopping venues and the amount of money they allocate for clothing.
Keywords: shopping behavior; fashion; clothing; social class; adults; zachowania zakupowe; moda; ubiór; klasa społeczna; dorośli